2001
DOI: 10.1081/ncn-100002430
|View full text |Cite
|
Sign up to set email alerts
|

CYCLOHEXENE NUCLEIC ACIDS (CeNA) FORM STABLE DUPLEXES WITH RNA AND INDUCE RNASE H ACTIVITY

Abstract: Cyclohexene nucleic acids (CeNA) were synthesized using classical phosporamidite chemistry. Incorporation of a cyclohexene nucleo-side in a DNA chain leads to an increase in stability of the DNA/RNA duplex. CeNA is stable against degradation in serum. A CeNA/RNA hybrid is able to activate E. Coli RNase H. resulting in cleavage of the RNA strand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 4 publications
0
15
0
Order By: Relevance
“…Ribose modifications are not limited to substitutions in structure; nucleic acid analogs with a modified structure of the furanose cycle, such as derivatives containing 6-membered (hexitol [HNA] Fisher et al, 2009, cyclohexenic [CeNA] Nauwelaerts et al, 2007, and altritol [ANA] Fisher et al, 2007 nucleic acids) and 7-membered rings (oxepanic nucleic acid [ONA] Sabatino and Damha, 2007), bicyclic (locked nucleic acids [LNA] Braasch et al, 2003, 2′-deoxymethanocarbanucleosides [MCs] Terrazas et al, 2011), tricyclic (tricyclo-DNA [tc-DNA] Goyenvalle et al, 2015), and acyclic (unlocked nucleic acid [UNA] Jensen et al, 2008; Langkjaer et al, 2009) derivatives, can protect siRNAs from the action of nucleases and in some cases (CeNA, LNA, and UNA) do not inhibit RNAi (Herdewijn and Juliano, 2007; Deleavey and Damha, 2012). Among the 6-membered nucleic acid derivatives, CeNA is most suitable for modifying siRNA, since its complementary interaction with RNA stabilizes the duplex, increasing the melting point by 1.5°C per modified base and increases the oligoribonucleotide resistance to degradation in serum (Wang et al, 2001). Bicyclic derivatives (LNA) can even more significantly increase the melting temperature of siRNA.…”
Section: Chemical Modifications Of Sirnamentioning
confidence: 99%
“…Ribose modifications are not limited to substitutions in structure; nucleic acid analogs with a modified structure of the furanose cycle, such as derivatives containing 6-membered (hexitol [HNA] Fisher et al, 2009, cyclohexenic [CeNA] Nauwelaerts et al, 2007, and altritol [ANA] Fisher et al, 2007 nucleic acids) and 7-membered rings (oxepanic nucleic acid [ONA] Sabatino and Damha, 2007), bicyclic (locked nucleic acids [LNA] Braasch et al, 2003, 2′-deoxymethanocarbanucleosides [MCs] Terrazas et al, 2011), tricyclic (tricyclo-DNA [tc-DNA] Goyenvalle et al, 2015), and acyclic (unlocked nucleic acid [UNA] Jensen et al, 2008; Langkjaer et al, 2009) derivatives, can protect siRNAs from the action of nucleases and in some cases (CeNA, LNA, and UNA) do not inhibit RNAi (Herdewijn and Juliano, 2007; Deleavey and Damha, 2012). Among the 6-membered nucleic acid derivatives, CeNA is most suitable for modifying siRNA, since its complementary interaction with RNA stabilizes the duplex, increasing the melting point by 1.5°C per modified base and increases the oligoribonucleotide resistance to degradation in serum (Wang et al, 2001). Bicyclic derivatives (LNA) can even more significantly increase the melting temperature of siRNA.…”
Section: Chemical Modifications Of Sirnamentioning
confidence: 99%
“…Another group of third generation antisense oligonucleotides are the morpholino oligonucleotides (MF) [13], that are DNA analogs in which the ribose has been replaced by a morpholino moiety. In the case of cyclohexene nucleic acids (CeNA) [14], the five-membered furanose ring is replaced by a six-membered ring. Tricyclo-DNA (tcDNA), conformationally constrained DNA analogue, constitutes another example of third generation AS-ONs.…”
Section: Chemical Structurementioning
confidence: 99%
“…Orgel and coworkers reported the template-directed polymerization of some of these nonnatural nucleic acids using 2-methylimidazole-activated hexitol and altritol guanosine monomers (Kozlov et al, 2000) to make hexitol and altriol nucleic acids (HNAs and ANAs, respectively). HNA and ANA oligomers (Figure 6) form antiparallel duplexes with complementary DNA or RNA oligomers with structures that closely resemble that of A-form double-stranded nucleic acids (Hendrix et al, 1997a, 1997b; Wang et al, 2001; Allart et al, 1999). The authors found it difficult to create HNA or ANA oligomers longer than tetramers by template-directed polymerization, which suggests that not all monomers that form stable double-helical polymers necessarily undergo efficient templated oligomeriza-tion.…”
Section: Nonenzymatic Translation Of Nucleic Acids Into Synthetic Polmentioning
confidence: 99%